Analisis Performa Protokol Routing Proaktif dan Reaktif pada MANET dengan Menggunakan OMNeT++ - Lala, Zefanya Loudewieq Gabriel; Widiasari, Indrastanti R. (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Mobile Ad-hoc Network (MANET) technology is a wireless network consisting of a random and dynamic set of nodes. Free flow and ever-changing nodes lead to unpredictable routes throughout the network, so a routing protocol is required to determine the path of each node. Therefore, a study was conducted to analyze the performance of routing protocols based on their characteristics, namely proactive and reactive. The proactive routing protocol tested is DSDV and the reactive routing protocol uses AODV. Based on the research conducted, it can be concluded that the reactive routing protocol, AODV, has better performance than the proactive routing protocol, DSDV, measured by three Quality of Service (QoS) parameters, namely Packet Delivery Ratio (PDR), throughput, and average delay.